Impact of Motivation and Temperament in Pre-School and School Setting. A Narrative Review - Kalogeratos, Gerasimos (Technium Education and Humanities, 2023)
Motivation and temperament are integral determinants of a child’s learning journey and social adaptation in early educational settings. This paper examines how intrinsic and extrinsic motivational factors influence engagement, curiosity, and academic outcomes, while also exploring the diverse temperamental profiles, peer interactions, and propensity for leadership that children exhibit. The unique interplay between motivation and temperament has profound implications for classroom dynamics, peer interactions, and the cultivation of foundational leadership traits. Recognizing and harnessing these influences can optimize individual learning experiences, fostering both academic growth and the development of essential life skills in young learners.